Inhibiting Glycogen Synthase Kinase 3 Reverses Obesity-Induced White Adipose Tissue Inflammation by Regulating Apoptosis Inhibitor of Macrophage/CD5L-Mediated Macrophage Migration. Issue 9 (September 2018) - Wang, Li; Wang, Yuan; Zhang, Chao; Li, Jingjing; Meng, Yuan; Dou, Man; Noguchi, Constance Tom; Di, Lijun
Abstract : Objective—: Obesity-induced inflammation in white adipose tissue, characterized by increased macrophage infiltration and associated with macrophage population shift from anti-inflammatory M2 to proinflammatory M1 macrophages, largely contributes to obesity-induced insulin resistance and influences type 2 diabetes mellitus pathogenesis. GSK3 (glycogen synthase kinase 3), a serine/threonine kinase, has been reported to participate in various cellular processes. We sought to examine the potential mechanism by which GSK3, a serine/threonine kinase implicated in various cellular processes, modulates obesity-induced visceral adipose tissue (VAT) inflammation. Approach and Results—: Male C57BL/6J mice were fed a high-fat diet for 10 weeks while being treated with vehicle control or GSK3 inhibitors SB216763 or CHIR99021. RNA-sequencing results using VAT demonstrated that GSK3 inhibitor treatment reversed obesity-specific expression of genes associated with inflammation. Consistently, GSK3 inhibition reduced obesity-induced VAT inflammation as characterized by decreased proinflammatory M1 macrophages but increased anti-inflammatory M2 macrophages in the VAT and reduced circulatory inflammatory monocytes. These anti-inflammatory effects of GSK3 inhibition were found to be driven, at least in part, by inhibiting production of apoptosis inhibitor of macrophage in macrophages via inactivating STAT3 to reduce free fatty acid and chemokine level produced from VAT to suppress the migration/chemotaxis of macrophages and monocytes. Conclusions—: Our findings suggest that GSK3 may act as an important regulator of obesity-induced inflammation and characterize the novel role of GSK3 in shifting macrophage polarization and reinforce its therapeutic potential for obesity-induced inflammation and its associated diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.